Optimal Multicarrier Multi-Hop Non-Regenerative MIMO Relays with QoS Constraints - Rong, Yue (IEEE, 2011)
In this paper, we derive the optimal source and relay matrices of a multicarrier multi-hop multiple-input multiple-output (MIMO) relay system that guarantee the predetermined quality-of-service (QoS) criteria be attained with the minimal total transmission power. We consider the linear minimal mean-squared error (MMSE) receiver at the destination node and show that the solution to the original optimization problem can be upper-bounded by using a successive geometric programming (GP) approach and lower-bounded by utilizing a dual decomposition technique. Simulation results show that both bounds are tight, and to obtain the same QoS, the proposed MIMO relay system requires substantially less power than that of the suboptimal relay scheme.